The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s12526-021-01237-1
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Paleodictyon patterns after simulated mining activity on Pacific nodule fields

Abstract: Since the late 1980s, various experiments have been conducted in polymetallic nodule fields of the Pacific Ocean to assess the potential environmental impacts of future mining, specifically in two areas: the Peru Basin and the Clarion-Clipperton Fracture Zone (CCZ). Two expeditions, SO242/2 in 2015 (Peru Basin) and SO268/1 + 2 in 2019 (CCZ), deployed a towed camera system to collect imagery from both areas. These expeditions aimed to assess recovery of fauna in the short (few weeks) and long term (several year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
(69 reference statements)
0
6
1
Order By: Relevance
“…The Aleutian examples are considerably smaller than the previously published examples, except for some specimens from the DEA (Fig. 2 e in Boehringer et al 8 ).…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…The Aleutian examples are considerably smaller than the previously published examples, except for some specimens from the DEA (Fig. 2 e in Boehringer et al 8 ).…”
Section: Discussioncontrasting
confidence: 59%
“…The density of Paleodictyon in the study area was considerably lower than the maximum densities (45 indiv./m 2 )found at the MAR 5 or along the Indian Ridge (9.7 indiv./m 2 ), where patchy distributions were observed 9 . Also, the densities in the Aleutian area were three orders of magnitude lower than the average values reported for the CCZ (0.3 indiv./m 2 in Durden et al 7 ; and 0.2 indiv./m 2 in Boehringer et al 8 ) but higher than those reported in the DISCOL Experimental Area (DEA) in the Southeastern Pacific (0.0033 indiv./m 2 in Boehringer et al 8 ). Mesh sizes (usually referred as diameter) reported in the literature span from 1.8 to 7.5 cm, with the average size always being more than 2.5 cm 5 9 .…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…26 years after the disturbance experiments the plough tracks were still very prominent and the impact on the fauna significant (e.g. Boetius and Haeckel, 2018, Stratmann et al, 2018, Simon-Lledó et al, 2019, Gausepohl et al, 2020, Vonnahme et al, 2020, Boehringer et al, 2021.…”
Section: Study Sitementioning
confidence: 99%